Developing an integrated library management system with agile methods, the University of Ibadan experience (2022)
Agile methods is the software development methodology and practices used in software industry in which the elements and principles of agile methods are used. Generally, the agile development process is an incremental work process that promotes the importance of customer satisfaction, collaboration, communication, teamwork, good quality and planned follow-up practices. The paper aims to discuss these issues. This paper first presents an overview of agile methods, addresses the most relevant ones for developing library management system then discusses the utilization of these methods in the context of the development of an integrated library management system presenting the case of Kenneth Dike Library, University of Ibadan. The Kenneth Dike Library, University of Ibadan after several attempts at automating its processes since the early 90’s eventually resolved to develop an in-house Library Automation System in 2015 using agile methods. The paper refers to definite initiatives taken to improve development processes as well as discuss the benefits and challenges when applying the agile methods in order to change traditional working culture and encourage end user participation in the building process. The following elements of agility can be considered the most effective and relevant: appreciating the needs of the customers, end-user participation and satisfaction, quality assurance, ability to redesign and make decisions fast and empowering the team, eliminating of waste. The paper finally highlights what the library can achieve by adapting a fresh approach for developing, evaluating and managing its operations and how the library staff can benefit from the agile way of working. Automation, Agile Development methods, Management, Quality, User satisfaction and University libraries